The optimal time for laparoscopic excision of ovarian endometrioma: a prospective randomized controlled trial - Qing Wu; Qingmei Yang; Yanling Lin; Lin Wu; Tan Lin (BMC, 2023)
Abstract Objective This study aimed to explore the optimal time of laparoscopic cystectomy for unilateral ovarian endometrioma patients and evaluate the influence on ovarian reserve. Materials and methods This prospective randomized controlled study included 88 women with unilateral ovarian endometrioma at a tertiary teaching hospital. All patients received their first identified diagnosis of ovarian endometrioma by ultrasound (> 4 cm and ≤ 10 cm) and were administered an oral contraceptive pill (OC) for one cycle before laparoscopy. They were randomly divided into two groups: laparoscopy at the late luteal phase (group LLP) (n = 44) (termination of OC for two days) and laparoscopy at the early follicular phase (group EFP) (n = 44) (day 3 after menstruation). Basic clinical characteristics were recorded. Serum Anti-Müllerian hormone (AMH) levels were measured at various times to predict ovarian reserve. Serum levels of Anti-Müllerian hormone (AMH) were measured at several time sites to predict the ovarian reserve; AMH and leukocyte esterase (LE) levels of the endometrioma wall were measured. Results Before surgery, serum AMH levels decreased in both groups from preoperative to one week and six months postoperatively. In contrast, the difference values of group EFP were larger than those of group LLP at postoperative one week and postoperative six months (1.87 ± 0.97 vs. 1.31 ± 0.93, P = 0.07; 1.91 ± 1.06 vs. 1.54 ± 0.93, P = 0.001). The mean rates of postoperative serum AMH decline were 37.92% and 46.34% in group EFP, significantly higher than those in group LLP (25.83% vs. 31.43%, P < 0.001). Ovarian endometrioma wall AMH of group LLP was significantly lower than that of group EFP ([22.86 ± 3.74] vs. [31.02 ± 5.23], P < 0.001). Meanwhile, ovarian endometrioma LE concentration of group LLP was significantly higher than that of group EFP ([482.83 ± 115.88] vs. [371.68 ± 84.49], P<0.001). There was also a significant inverse correlation between leukocyte esterase and AMH concentration in an ovarian endometrioma cyst wall (r=-0.564, P<0.001). Conclusion(s) The optimal time for laparoscopic cystectomy for patients with first identified unilateral ovarian endometrioma is the late luteal phase, which reduces ovarian tissue loss and preserves ovarian reserve effectively and safely.